THE EFFECT OF FINANCIAL PERFORMANCE AND COMPANY SIZE ON SHARIA STOCK LISTED IN JAKARTA ISLAMIC INDEX - Eva Nurlita; Robiyanto Robiyanto (Politeknik Caltex Riau, 2018)
Financial performance is usually measured using a ratio that has several weaknesses that can't measure by value and need a comparison. There are new alternatives that measure performance based on value and are still rarely used specifically in stocks based on Islamic law. This study aims to find and obtain empirical evidence concerning the influence of Economic Value Added, Market Value Added, Financial Value Added and the size of the company to the stock price of sharia companies listed in the Jakarta Islamic Index period 2014-2016. By using purposive sampling, obtained sample of 13 sharia stocks observed in annual period, hence obtained panel data as much as 39. Data analyzed by using doubled linear regression. The results showed that Market Value Added has a significant positive effect on stock prices. EVA, FVA, and firm size have no significant effect on stock prices. Economic Value Added, Market Value Added, Financial Value Added and company size together have a significant effect on stock price.